Collaboration between Zakat Organizations and Universities in Enhancing the Economy of Ummah - Saleh, Khairul -; Kurniani, Kurniani -; Utami, Hadiahti -; Pratiwi, Mona Inayah (Admisi dan Bisnis, 2024)
The purpose of this research is to know and examine further the principles, values and ethics, processes, and mechanisms of cooperation between Lazis Nurul Huda and University in improving the people”™s economy in Surakarta City, Central Java through the management of zakat, infaq, shodaqoh, and waqf in Higher Education. Also, this research discusses the challenges in maximizing the potential of zakat in Indonesia due to the informal collection process and the need for professional management. This research uses qualitative methods with case studies. Then the data needed is primary data through depth interviews. The findings of the research can be useful for Lazis Nurul Huda in improving its coordination with University UNS in managing zakat, as well as for other zakat organizations in establishing partnerships with, through scholarship and education program for mustahik in university. The research suggests that universities can contribute to this by establishing zakat management institutions, which can work in partnership with zakat organizations to improve the distribution of zakat and increase awareness among the public about the importance of zakat.